PELATIHAN KADER DAN GURU PAUD WILAYAH KERJA PUSTU TENDA UNTUK DETEKSI DINI PERKEMBANGAN ANAK USIA DINI DENGAN DEVELOPMENT DENVER SCRENING TEST (DDST) - Maria Getrida Simon Simon; Yohana Hepilita; Lusia Henny Maryati; Alberika S.D. Jehoman; Dorotea Nasvia; Fredheric C. Brosnan; Maria Natasya Madur; Felomena Murni (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
This community service aims to provide education to teachers and parents as well as to monitor the growth and development of toddlers. Monitoring child development is useful for finding deviations / obstacles to children's development from an early age, so that prevention, stimulation and healing and recovery efforts can be provided with clear indications as early as possible during critical times of growth and development. And one method that can be used for screening / monitoring child development is the DDST (Denver Development Screening Test) method. The activities carried out were counseling and DDST training. This activity will involve the active role of cadres and teachers who have attended the DDST training. This training is important to do to increase the participation of cadres in increasing knowledge about child development and early detection of any abnormalities experienced by children so that later children can be stimulated more quickly if they feel that they are lacking in one area achievement